Diagnostic accuracy of touch imprint cytology for head and neck malignancies: a useful intra-operative tool in resource limited countries. Issue 1 (December 2017) - Naveed, Hania; Abid, Mariam; Hashmi, Atif; Edhi, Muhammad; Sheikh, Ahmareen; Mudassir, Ghazala; Khan, Amir
Abstract Background Intraoperative consultation is an important tool for the evaluation of the upper aerodigestive tract (UAT) malignancies. Although frozen section analysis is a preferred method of intra-operative consultation, however in resource limited countries like Pakistan, this facility is not available in most institutes; therefore, we aimed to evaluate the diagnostic accuracy of touch imprint cytology for UAT malignancies using histopathology of the same tissue as gold standard. Methods The study involved 70 cases of UAT lesions operated during the study period. Intraoperatively, after obtaining the fresh biopsy specimen and prior to placing them in fixative, each specimen was imprinted on 4-6 glass slides, fixed immediately in 95% alcohol and stained with Hematoxylin and Eosin stain. After completion of the cytological procedure, the surgical biopsy specimen was processed. The slides of both touch Imprint cytology and histopathology were examined by two consultant histopathologists. Results The result of touch imprint cytology showed that touch imprint cytology was diagnostic in 68 cases (97.1%), 55 (78.6%) being malignant, 2 cases (2.9%) were suspicious for malignancy, 11 cases (15.7%) were negative for malignancy while 2 cases (2.9%) were false negative. Amongst the 70 cases, 55 cases (78.6%) were malignant showing squamous cell carcinoma in 49 cases (70%), adenoid cystic carcinoma in 2 cases (2.9%), non-Hodgkin lymphoma 2 cases (2.9%), Mucoepidermoid carcinoma 1 case (1.4%), spindle cell sarcoma in 1 case (1.4%). Two cases (2.9%) were suspicious of malignancy showing atypical squamoid cells on touch imprint cytology, while 13 cases (18.6%) were negative for malignancy, which also included 2 false negative cases. The overall diagnostic accuracy of touch imprint cytology came out to be 96.7% with a sensitivity and specificity of 96 and 100%, respectively while PPV and NPV of touch imprint cytology was found to be 100 and 84%, respectively. Conclusion Our experience in this study has demonstrated that touch imprint cytology provides reliable specific diagnoses and can be used as an adjunct to histopathology, particularly in developing countries, where the facility of frozen section is often not available, since a rapid preliminary diagnosis may help in the surgical management planning.